Modelowanie czynnika ludzkiego w przedsiębiorstwie - selekcja menedżerów. Studium przypadku azjatyckiej firmy Crompton Greaves LTD. - cz. 1 - Liniewicz, Patrycja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article stresses the importance of human resources amongst other organizational resources, as the base factor of organizational success. Thus it gives the priority to human resources in organizational management. The aim of this article is to share author's observation acquired in Asian culture, and alight possibility of modeling human resources in organizations, throughout using the selection and recruitment processes as the preliminary and introductory phase. The author states that set of valid and reliable tools enables forming the required profile of human resources. Extremely important for any selection process is to build accurate competence profiles, hence the issue is pointed in two-dimension perspective: job description related factors and organizational ones. Furthermore, the article describes different approaches to human competences, such as cognitive skills and personality. It is also required that listed characteristics are to be taken into evaluation during the selection process. The author presents the theory on the basis of experience acquired during observation held in Human Resources Department in Crompton Greaves Ltd., Bombay, India. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 289-303